FATIGUE RESISTANCE of TUBULAR JOINT TYPE-T AT OFFSHORE STRUCTURE - TAUFAN TUKUBOYA (NIM : 25003003); Pembimbing : Prof.Ir.Amrinsyah Nasution, MSCE,PhD, MOHAMMAD
Joint structure fatigue at offshore construction was very influenced by level of cyclic load and factor of sea-water corrosion especially at joint type which have owned initial micro crack. This thesis study about relation of cyclic and sea-water corrosion to fatigue resistance of tubular joint type-T [at] offshore structure. Research conducted by using 3-dimension finite element models from tubular joint type-T [at] offshore structure and analysed to value of wave (sea) load design with 25 years return periods and also the nature of corrosivity in territorial water of Indonesia sea. Result of analysis use Ansys software and theory of fracture mechanics indicate that fatigue life of structure will linearly decrease equal to crack depth. At similar of cyclic load design, structure fatigue resistance evaluated from amount of cycle causing final crack at tubular joint type-T which have owned initial crack 0.25 mm under corrosion less of about 47.7% (average value) from structure fatigue resistance without corrosion. Relation between aksial load capacities of structure and crack depth can be expressed with equation : σ= - 16.565 ln (a / tp) - 85.154 with a = crack depth (mm) and, tp = pipe thickness (mm). Meanwhile the relation mount degradation of structure capacities momen at various crack depth expressed with equation following : Mkap = - 1.0999 (a / tp)3 + 11.439 (a / tp)2 Ã‚Â– 40.348 (a / tp)-31.28